Türkiye’de Düzensiz Göçmenler, Geçici Korunanlar Ve Uluslararası Korunanlar - Karakaya, Şeyma (Göç ve Sosyal Hizmet, 2023)
Turkey has become a target country for immigrants in recent years. Turkey evaluates foreigners passing through its borders in two ways. These are regular (legal) and irregular (illegal) immigrants. Turkey grants national or international protection status to immigrants it accepts as legal immigrants. Refugee, conditional refugee and subsidiary protection are international protection statuses. These types of protection are guaranteed by international instruments such as the Geneva Convention and the 1967 Protocol. The type of protection that Turkey provides at the national level is temporary protection. Turkey grants this status to persons crossing its borders in groups and in need of immediate protection. Turkey uses the term irregular immigrant for people who cross its borders illegally or stay illegally. These people who come with illegal immigration are caught and kept under administrative detention in repatriation centres. Irregular immigrants, for whom a deportation decision is issued as a result of administrative detention, are deported. In this part of the book, first of all, irregular migrants, then Syrians under temporary protection and finally those with international protection status will be discussed.